2006
DOI: 10.1016/j.immuni.2006.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Human Tyrosine Kinase 2 Deficiency Reveals Its Requisite Roles in Multiple Cytokine Signals Involved in Innate and Acquired Immunity

Abstract: Tyrosine kinase 2 (Tyk2) is a nonreceptor tyrosine kinase that belongs to the Janus kinase (Jak) family. Here we identified a homozygous Tyk2 mutation in a patient who had been clinically diagnosed with hyper-IgE syndrome. This patient showed unusual susceptibility to various microorganisms including virus, fungi, and mycobacteria and suffered from atopic dermatitis with elevated serum IgE. The patient's cells displayed defects in multiple cytokine signaling pathways including those for type I interferon (IFN)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
471
3
19

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 614 publications
(507 citation statements)
references
References 49 publications
(86 reference statements)
14
471
3
19
Order By: Relevance
“…TSLP is known to initiate typical IgE-and T H 2 cell-dependent allergic diseases through its effects on dendritic cells, whereas its ability to potently stimulate MCs might contribute to the T cell-and IgE-independent allergic inflammation. 4,5 In agreement with a previous study, 6 here we show that primary human BSM cells from nonasthmatic donors (commercially 5 with or without antibody to TNF or isotype control (10 mg/mL each). Data are representative of 4 experiments.…”
Section: To the Editorsupporting
confidence: 92%
See 1 more Smart Citation
“…TSLP is known to initiate typical IgE-and T H 2 cell-dependent allergic diseases through its effects on dendritic cells, whereas its ability to potently stimulate MCs might contribute to the T cell-and IgE-independent allergic inflammation. 4,5 In agreement with a previous study, 6 here we show that primary human BSM cells from nonasthmatic donors (commercially 5 with or without antibody to TNF or isotype control (10 mg/mL each). Data are representative of 4 experiments.…”
Section: To the Editorsupporting
confidence: 92%
“…3,4 In addition, homozygous mutations in the tyrosine kinase 2 gene are the genetic defect in a subgroup of patients with HIES. 6 The K531E mutation described in this report is the first mutation in the linker domain of STAT3, further expanding the genetic heterogeneity of HIES. According to recent studies, 4,7,8 patients with HIES with STAT3 mutations showed absent or markedly decreased levels of T H 17 cells in their peripheral blood.…”
mentioning
confidence: 66%
“…Recently, a patient with homozygous mutation of Tyk2, which causes a loss of Tyk2 protein, was reported (25). The patient was clinically diagnosed as hyper IgE syndrome and showed susceptibility to various types of pathogens including virus, fungi, and intracellular and extracellular bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Similarly, JAK1 deficiency is associated with decreased lymphocyte development through defects in type I (IFN-a) and type II (IL-2) cytokine signaling, whereas human TYK2 deficiency is associated with impaired antimicrobial and allergic responses indicating important roles of these family members in the regulation of key aspects of immune cell development and maintenance. 6,7 In contrast, JAK2 has been implicated in erythropoiesis through its association with the selective association with the single chain cytokine receptor, erythropoietin receptor (EPO-R). 8 Myeloproliferative neoplasms (MPNs) are clonal malignancies characterized by the uncontrolled expansion of multipotent hematopoeitc progenitor cells.…”
Section: Introductionmentioning
confidence: 99%